2022
DOI: 10.1021/acs.iecr.2c03488
|View full text |Cite
|
Sign up to set email alerts
|

Phase Equilibria and Mechanism Insights into the Separation of Isopropyl Acetate and Methanol by Deep Eutectic Solvents

Abstract: Separation of methanol−isopropyl acetate (IPAC) obtained via isopropanol synthesis is essential. Deep eutectic solvents (DESs) have garnered extensive attention in the field of azeotropic separation owing to their advantages such as biodegradability, ecofriendliness, and cost-effectiveness. In this work, three cholinebased DESs were prepared. Then, the experimental data of the synthesized DESs with methanol and IPAC were measured, which were linearly correlated with Hand and Othmer−Tobias equations. The G M /R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…To eliminate the effects of repulsive forces, the energy of the virtual box is minimized. After reaching the specified temperature of the system, it is necessary to equilibrate in the NPT ensemble for 50 ns, with data saved every 5 ps . VMD is used to analyze the structural characteristics of the extraction process.…”
Section: Experiments and Methodsmentioning
confidence: 99%
“…To eliminate the effects of repulsive forces, the energy of the virtual box is minimized. After reaching the specified temperature of the system, it is necessary to equilibrate in the NPT ensemble for 50 ns, with data saved every 5 ps . VMD is used to analyze the structural characteristics of the extraction process.…”
Section: Experiments and Methodsmentioning
confidence: 99%
“…Moreover, MD simulation has also made some progress in the analysis of the mechanism of LLE. 24 Chen et al 25 used MD simulation to elucidate the basic mechanism of acetone-methanol azeotrope separation using ILs and found that the strong interaction between methanol and dimethylphosphate was responsible for the azeotrope elimination. Dai et al 26 Screening of ILs.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The results showed that the key to the separation is the strong hydrogen bond between the O atom of the anion in the ILs and the H atom in TFP. Moreover, MD simulation has also made some progress in the analysis of the mechanism of LLE . Chen et al used MD simulation to elucidate the basic mechanism of acetone-methanol azeotrope separation using ILs and found that the strong interaction between methanol and dimethylphosphate was responsible for the azeotrope elimination.…”
Section: Introductionmentioning
confidence: 99%